2012
DOI: 10.17221/48/2011-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and efficiency of large and small field crop farms and mixed farms of the old and new EU regions

Abstract: Abstract:The main aim of the paper is to consider the question whether a higher specialization and a bigger economic size class of farms determine a higher technical efficiency at the same scale for the farms from the new and old countries of the EU. This study is based on the data contained in the Farm Accounting Data network and covers the first four years following the extension of the European Union in 2004. The adopted units comprised average farms representing 80 regions belonging to eleven countries of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 19 publications
2
23
0
1
Order By: Relevance
“…What is more, Gorton and Davidova (2004) claimed, what is revealed in practice, that mean farm size increases and that larger farms are more profitable and efficient. These observations are also supported by our earlier paper (Błażejczyk-Majka, Kala, Maciejewski, 2011), which confirms that the highest efficiency is achieved by the biggest farms and that a longer period of farming under stable conditions promotes a higher efficiency. At the same time, Kleinhanß et al (2007) observed that enlargement of farms focused on animal production is limited by EU requirements connected with environmental protection and that environmental adaptation and efficiency have become key issues in the new European agricultural policy.…”
Section: Introductionsupporting
confidence: 86%
“…What is more, Gorton and Davidova (2004) claimed, what is revealed in practice, that mean farm size increases and that larger farms are more profitable and efficient. These observations are also supported by our earlier paper (Błażejczyk-Majka, Kala, Maciejewski, 2011), which confirms that the highest efficiency is achieved by the biggest farms and that a longer period of farming under stable conditions promotes a higher efficiency. At the same time, Kleinhanß et al (2007) observed that enlargement of farms focused on animal production is limited by EU requirements connected with environmental protection and that environmental adaptation and efficiency have become key issues in the new European agricultural policy.…”
Section: Introductionsupporting
confidence: 86%
“…Kleinhanss et al in 2007 have pointed out that some pivotal relationships exist between the efficiency and the farm size; in fact, these scholars have highlighted that there is a positive role of financial supports, allocated by the Common Agricultural Policy, towards the productive specialization and efficiency, corroborating the theoretical framework, in a sample of farms belonging to the FADN dataset, related to a specific nexus between the productive specialization or economic size and technical efficiency (Błażejczyk-Majka et al 2011).…”
Section: Literature Reviewmentioning
confidence: 72%
“…In Kosovo, there may be a mixture of farmers growing greenhouse tomatoes or peppers as a single crop and those who may have other crops with tomatoes or peppers in the same greenhouse. Large-sized and mixed farms tend to have high efficiency [13]. The variable T/PFARM i can be important given that product prices in agriculture have a high tendency to vary [44].…”
Section: Regression Analysismentioning
confidence: 99%